Isolation of xet gene involved in wood formation in shorea parvifolia dyer pervioflia - Chia, Sze Wooi (Universiti Malaysia Sarawak, (UNIMAS), 2005)
Wood formation genes played an important internal factor besides the hormonal aspects in xylogenesis, which control the development of secondary growth in trees. One of the identified enzymes, xyloglucan endotransglycosylase (XET), is discovered to modify intermicrofibrillar xyloglucan chains, a major component of primary cell walls in dicots to allow wall-loosening required for plant cell expansion. In this study, Shorea parvifblia Dyer parvifolia obtained from Sarawak Forest Seed Bank was chosen due to its economical value and strong adaptability. The total genomic DNA was extracted using a modified CTAB method. A pair of primers, i. e. forward primer (5' - TGGTGACTCAGCTGGAACAG - 3') and reverse primer (5' - AATCATCGGCATTCCATAGG - 3') was constructed based on the known XFT mRNA sequences obtained from the databases. Polymerase Chain Reaction (PCR) was performed based on the optimized thermo-cycling profile as follow: 35 cycles of I min of denaturing at 94°C, 1 min of annealing at 46°C, and 2 min extension phase at 72°C. A DNA fragment of - -527bp was obtained from the amplification and was cloned using a TA-vector system. Then, the isolated and purified plasmid was sent for sequencing.